2022
DOI: 10.1186/s12882-022-03017-w
|View full text |Cite
|
Sign up to set email alerts
|

Perception of social inequities in the access to the kidney transplant waiting list by nephrology trainees: a national survey

Abstract: Background Social inequalities in health are responsible for disparities in access to the kidney transplant waiting list (KTWL). The perception of disparities by nephrologists has consequences for the registration on the KTWL. The purposes of our study were to assess the perception of the factors implicated in the disparities in access to the KTWL by nephrology trainees and to assess the quality of the questionnaire. Methods A questionnaire was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Studies have shown that clinicians did not identify gender as a determinant of inequities in access to kidney transplantation. 22,23 We aimed to describe the perspectives of nephrologists on gender disparities in access to kidney transplantation, which may inform strategies to improve access to kidney transplantation for patients with kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that clinicians did not identify gender as a determinant of inequities in access to kidney transplantation. 22,23 We aimed to describe the perspectives of nephrologists on gender disparities in access to kidney transplantation, which may inform strategies to improve access to kidney transplantation for patients with kidney failure.…”
Section: Introductionmentioning
confidence: 99%